Natural fiber reinforced polylactic acid composites: a review - Siakeng, Ramengmawii; Jawaid, Mohammad; Ariffin, Hidayah; S. M., Sapuan; Asim, Mohammad; Saba, Naheed (Society of Plastics Engineers, 2018)
Biopolymer-based composites have attracted the attention of researchers and industries due to their eco-friendliness and environmental sustainability, as well as their suitability for a number of applications. Biocomposites containing natural fibers and biopolymers would be the ideal choice in the development of biodegradable materials for different applications. Polylactic acid (PLA) is an environmentally interesting biopolymer, which also has exclusive qualities, such as good transparency and processability, glossy appearance, and high rigidity, although it has some shortcomings as well, for example, its brittleness and high rate of crystallization. PLA-based natural fiber composites are entirely bio-based materials with promising biodegradability and mechanical properties. Several research studies have been carried out on PLA and its composites to explore their potential to substitute petroleum-based products, but until now there is no comprehensive review with up-to-date research data available in the literature. The aim of this review is to highlight the trends in the research and development of PLA and PLA-based natural fiber composites over the past few years. This review article covers current research efforts on the synthesis and biodegradation of PLA, its properties, trends, challenges and prospects in the field of PLA and its composites. PLA-based composites are moderately abundant; and further research and development is needed for cost reduction and broader utilization.